OLD STATE IN THE NEW GOVERNMENT: VICTORY STRATEGY FOR CANDIDATES FOR LEGISLATIVE MEMBERS OF THE DPRD DAPIL 3 ELECTED - Azen Sayena; Harto, Unggul Sugi; Habibullah, Akhmad (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2024)
The 2024 general election with an open proportional system has led to tight competition between legislative candidates in their electoral district. To win the election, legislative candidates compete with each other in one party or with legislative candidates from other parties. This competition causes legislative candidates to compete in strategies, tactics and winning methods. So this has become a new phenomenon that occurred during the 2024 legislative election yesterday where the competition between legislative candidates from one party is interesting to study. As was done by Muhamad Rizki Nurohman, a legislative candidate from the PDIP party, Electoral District III, Brebes Regency DPRD. Therefore, the purpose of this study is to find out how the competition is between legislative candidates from the PDIP party, Electoral District III, Brebes Regency. And what strategies were carried out by Muhamad Rizki Nurohman in an effort to win the 2024 legislative election and what is the role and position of the party in the competition. This research method uses a qualitative method with a Case Study approach. The data source in this study uses primary data obtained from direct interviews with Muhamad Rizki Nurohman, a member of the Brebes Regency DPRD and the Chairperson of the Brebes Regency PDIP DPC, KH. Imam Hasyim and participant observation. The results of the study show that the strategies carried out by Muhamad Rizki Nurohman, first, social capital strategy, namely the person or figure is known by the constituents. Second, Prioritizing the approach to local community leaders and party administrators from the RT, RW, Sub-district and other community leaders. Third, Utilizing the PDIP mass support base in electoral district III, even Muhamad Rizki serves as the chairman of Kick Boxing Indonesia in Brebes Regency. Fourth, populist strategy, namely a work program that is more pro-people.